Heat transfer enhancement in pillow-plate heat exchangers with dimpled surfaces: A numerical study. (5th May 2019) - Piper, M.; Zibart, A.; Djakow, E.; Springer, R.; Homberg, W.; Kenig, E.Y.
Highlights: A secondary structuring of the pillow-plate surface with dimples was suggested. CFD-based analysis of the new structured surface was performed. Dimples initiate regular disturbances of the turbulent boundary layer and hence improve mixing near the wall. The thermo-hydraulic efficiency in the newly restructured pillow-plate channel is significantly increased. Abstract: Pillow-plate heat exchangers (PPHE) represent an innovative, fully welded plate-type heat exchanger. They consist of a stack of panels, which are characterized by "pillow-like" surface. The waviness of the channels enhances mixing in the fluid boundary layers, which consequently augments heat transfer. However, PPHE need further optimization in order to compete with corrugated plate heat exchangers with respect to compactness. In this study, a method to enhance heat transfer in PPHE is proposed, based on a surface modification of pillow plates by secondary dimple structures on their primary wavy surface. The new structured surface of the pillow plates promotes stronger near-wall mixing.